Rates of Serious Intracellular Infections in Autoimmune Disease Patients Receiving Initial Glucocorticoid Therapy - Migita, Kiyoshi (Public Library of Science, 2013)
BACKGROUND/AIMS: The Japanese National Hospital Organization evidence-based medicine (EBM) Study group for Adverse effects of Corticosteroid therapy (J-NHOSAC) is a Japanese hospital-based cohort study investigating the safety of the initial use of glucocorticoids (GCs) in patients with newly diagnosed autoimmune diseases. Using the J-NHOSAC registry, the purpose of this observational study is to analyse the rates, characteristics and associated risk factors of intracellular infections in patients with newly diagnosed autoimmune diseases who were initially treated with GCs. METHODOLOGY/PRINCIPAL FINDINGS: A total 604 patients with newly diagnosed autoimmune diseases treated with GCs were enrolled in this registry between April 2007 and March 2009. Cox proportional-hazards regression was used to determine independent risk factors for serious intracellular infections with covariates including sex, age, co-morbidity, laboratory data, use of immunosuppressants and dose of GCs. Survival was analysed according to the Kaplan-Meier method and was assessed by the log-rank test. There were 127 serious infections, including 43 intracellular infections, during 1105.8 patient-years of follow-up. The 43 serious intracellular infections resulted in 8 deaths. After adjustment for covariates, diabetes (Odds ratio [OR]: 2.5, 95% confidence interval [95% CI] 1.1–5.9), lymphocytopenia (≦1000/μl, OR: 2.5, 95% CI 1.2–5.2) and use of high-dose (≧30 mg/day) GCs (OR: 2.4, 95% CI 1.1–5.3) increased the risk of intracellular infections. Survival curves showed lower intracellular infection-free survival rate in patients with diabetes, lymphocytopaenia and high-dose GCs treatments. CONCLUSIONS/SIGNIFICANCE: Patients with newly diagnosed autoimmune diseases were at high risk of developing intracellular infection during initial treatment with GCs. Our findings provide background data on the risk of intracellular infections of patients with autoimmune diseases. Clinicians showed remain vigilant for intracellular infections in patients with autoimmune diseases who are treated with GCs.